Meningkatkan Kompetensi Pedagogik Pendidik dan Kepala Sekolah dalam Implementasi Kurikulum 13 di PAUD Merah Delima Jakarta Utara - Hasnah Hasnah (Neolectura, 2022)
This research is a School Action Research conducted by PAUD Supervisors in the Kelapa Gading Jakrta Utara District. The purpose of this study is to determine the effectiveness of improving the Pedagogic Competence of Educators and Principals in the Implementation of Curriculum 13. In this study using survey techniques. The research was conducted in three stages, namely preparation, implementation, evaluation and reflection which were carried out in at least two cycles. In the preparation stage, a scenario of activities, schedules, times, places and other supporting facilities such as observation sheets, and questionnaires is made. From the results of the study, data obtained from the research results in this school action research activity carried out in 2 cycles, that the academic supervision carried out by the principal assisted by the ECCE Supervisor for 5 teachers who did not have a teacher education background, succeeded in increasing their pedagogical competence in compiling Learning Planning in improving the implementation of Curriculum 13. Pedagogic abilities can be carried out regularly so that ECCE teachers can continue to improve the teaching abilities of students creatively and innovatively and can also be carried out on all teachers in rotation and concern all aspects of teacher abilities and competencies as required in Permendiknas No. 16 of 2007.